Ex Appeal: Current Relationship Quality and Emotional Attachment to Ex-Partners. (March 2013) - Spielmann, Stephanie S.; Joel, Samantha; MacDonald, Geoff; Kogan, Aleksandr
Relationship research typically treats feelings about current romantic partners as independent of any lingering attachment to past partners. In contrast, the current study tests for an inverse association between current relationship quality and attachment to ex-partners. A longitudinal study followed individuals in relationships at three points over the course of 6 months. Participants reported their current relationship quality, emotional attachment to ex-partners, and perceived quality of relationship alternatives. Longitudinal declines in relationship quality predicted increased longing for ex-partners, above and beyond attention to relationship alternatives more generally. On the other hand, increased longing for ex-partners over time predicted decreased relationship quality, but only among those considering recent ex-partners. These findings suggest that ex-partners may be used in a substitution process to bolster belongingness needs when relationships sour and that resolving feelings for one's most recent ex may be important for maximizing a new relationship's potential.